INVESTIGATING THE RELATIONSHIPS BETWEEN ASEAN STOCK MARKETS: AN APPROACH USING THE GRANGER CAUSALITY TEST OF TIME-VARYING INFORMATION EFFICIENCY - Trần Thị Tuấn Anh (Tạp chí Khoa học Đại học Đà Lạt)
The information efficiency and the relationships between ASEAN stock markets are two of the issues that are of great research interest. However, these two issues were often investigated separately in previous studies. Therefore, this paper combines these two issues in the same analysis. Data on the daily closing index of six ASEAN stock markets, including Indonesia, Malaysia, the Philippines, Singapore, Thailand, and Vietnam are used to calculate Shannon entropy to measure the stock market information efficiency. In addition, this paper conducts the Granger causality test to reveal the relationships between the ASEAN stock markets. The results show that all six stock markets are not in the state of information efficiency, which means the stock indices, stock returns, and volatility are not purely random, but patterned. In addition, the Granger test results show that the ASEAN stock markets are logically correlated. The two markets that are more integrated than the others are Indonesia and Malaysia. Vietnam participates in regional economics in a passive way, while the Philippines is more proactive. The Singapore stock market is also less integrated with the other ASEAN markets, although it is a mature stock market that outperforms the rest.